Dynamic scapulohumeral rhythm: Comparison between healthy shoulders and those with large or massive rotator cuff tear - Naoya Kozono; Naohide Takeuchi; Takamitsu Okada; Satoshi Hamai; Hidehiko Higaki; Takeshi Shimoto; Satoru Ikebe; Hirotaka Gondo; Takahiro Senju; Yasuharu Nakashima (Journal of Orthopaedic Surgery, 2020)
Introduction: Assessment of scapular kinematics and the dynamics of the scapulohumeral rhythm (SHR) would be important for understanding pathologies of the shoulder and to inform treatment. Our aim in this study was to evaluate the SHR and scapular kinematics in patients with a rotator cuff tear (RCT), compared to a control group with healthy shoulders using image-matching techniques. Materials and Methods: The shoulder kinematics of large or massive RCT patients were evaluated and compared to a control group with healthy shoulders. Radiographic surveillance was performed throughout the full range of external rotation and scapular plane abduction. Computed tomography imaging of the shoulder complex was performed, with three-dimensional image reconstruction and matching to the radiographs to measure three-dimensional positions and orientations. SHR and angular values of the scapula were measured. Results: Scapular external rotation in the late phase of external rotation movement was greater in the RCT group than in the control group ( p < 0.05), but with no difference in the SHR. During scapular plane abduction, there were significant differences in SHR, scapular posterior tilt and scapular upward rotation between the RCT and control group ( p < 0.05). Conclusions: Regarding clinical relevance, this study clarified the differences of SHR and angular values of the scapula between the RCT and control group. These results underline the importance of assessment the SHR and scapular kinematics in individuals with a RCT. RCT is associated with specific compensation in the kinematics of the scapula and SHR during external rotation and scapular plane abduction, which could inform treatment.